Peran Kepemimpinan dalam Meningkatkan Pelayanan Publik : Studi Kasus PT Pelindo III Cabang Bima - Nike Ardiansyah (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This research aims to understand the leadership challenges in improving public services at PT Pelindo III Bima Branch, given the complexities faced, such as resistance from team members, operational pressures, ineffective internal communication, and the importance of relationships with local government. To achieve this objective, the research employs a descriptive qualitative method with a purposive sampling approach, where key informants include the Head of PT Pelindo III Bima Branch and various other stakeholders. Data was collected through in-depth interviews, direct observations, and documentation to gain a comprehensive understanding of the leadership dynamics in the field. Qualitative descriptive analysis was used to reduce and present the data, resulting in accurate findings regarding leadership effectiveness in this context. The study results indicate that leadership at PT Pelindo III Bima Branch faces significant challenges, particularly in managing change, improving internal communication, and building good relationships with local government. However, by implementing appropriate leadership strategies such as developing a clear vision, effective human resource management, and adapting to change, leaders can overcome these obstacles and enhance overall public service performance. In conclusion, effective leadership is key to ensuring that PT Pelindo III Bima Branch can meet the needs of port service users and contribute positively to the local economy.